2006
DOI: 10.1007/s00404-006-0269-1
|View full text |Cite
|
Sign up to set email alerts
|

Malon dialdehyde, nitrite and adrenomedullin levels in patients with premenstrual syndrome

Abstract: Even though various stress symptoms are present in PMS, there is no change in the levels of MDA, an oxidative distress indicator but AM and NO may have a pathophysiological role on this enigmatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…The increment in AM levels may be the result of a compensatory mechanism, and thus, may be a response to vascular reaction rather than oxidative distress 16 . Although the mechanism by which AM carries out its functions have not been fully clarified, it is thought that stimulation of the NO synthesis is one of the mechanisms 17 . Hattori et al.…”
Section: Discussionmentioning
confidence: 99%
“…The increment in AM levels may be the result of a compensatory mechanism, and thus, may be a response to vascular reaction rather than oxidative distress 16 . Although the mechanism by which AM carries out its functions have not been fully clarified, it is thought that stimulation of the NO synthesis is one of the mechanisms 17 . Hattori et al.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our a priori hypothesis, MDA levels were significantly higher during the first three weeks of the cycle as compared with day 28 while there was no significant association with PMS/MCAS. Two previous studies found no significant differences in MDA levels between PMS patients and controls (Balat et al, 2007;Duvan et al, 2011).…”
Section: Discussionmentioning
confidence: 66%
“…assessed the antioxidants levels such as glutathione, ceruloplasmin, SOD and lipid peroxidation product-MDA in PMS. They did not find any significant differences between the control and the PMS women in terms of antioxidant levels 26,27 . On the other hand, some studies reported that TAC levels in luteal phase were decreased in PMS women 1,5 .…”
Section: Discussionmentioning
confidence: 82%
“…Although estrogen is a potent antioxidant, its excessive activity in the luteal phase of PMS women may stimulate its pro-oxidant property leading to reduced TAC levels in these women 27,28 . Therefore, neuronal membrane dysfunction can be secondary to free radical-mediated pathology through toxic effects of free radicals on high ratio of polyunsaturated fatty acid in neuronal membrane, and may affect GABAergic system in PMS women 1 .…”
Section: Discussionmentioning
confidence: 99%